PENTINGNYA HOUSEKEEPING BAGI SUATU HOTEL - Parsidi, Parsidi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2004)
The general public tends to think of Housekeeping as the Department that : makes the head, empties the asthray and waste basked, tidies up the bathroom and leaves fresh towels. The truth of the matter is of course that it takes more manpower to accomplish. Housekeeping's almost countless function than those of any ather Department in the lodging industry. Housekeeping's responsibility may begin with fabrics, and progress to the selection and purchase of all furniture and furnishings; it encompasses not only their cleaning but their maintenance, repair, refurbishment and eventual replacement. Areas of concern include : sleeping rooms, meeting rooms, halls andelevator, all considered "front of the house" The designation also includes all other public area from lobbies to washrooms to restaurant and cocktail lounges. Out door areas such as pools and patios. Housekeeping also oversees almost the enttres "back of the house", from locker rooms to employee dinning, virtually everything.